Pacing strategy in men's 400 m hurdles accounting for temporal and spatial characteristics of elite athletes - Iskra, J.; Matusinski, A.; Otsuka, M.; Guex, K. (Journal of Human Kinetics, 2021)
The final result in a 400 m hurdles race (400mH) is relat ive to the motor preparation, technique of clearing hurdles as well as the adopted strategy of the race, including temporal aspects (split times in particular parts of the race) and spatial elements (the number of strides taken between subsequent hurdles). The objective of the study was to identify an optimal strategy for the 400mH race, including the stride pattern and split times. Data employed for this study were derived from results of 273 races held during the men`s finals of international events (Olympic Games, World and European Championships) held from 1968 to 2015. To determine the strategies in the race, three main hurdle sections were identified - 1-4H, 4-7H and 7-10H. In each part, the fa st (best results), avera ge and slow (worst results) performing groups of hurdlers were distinguished. The analysis of adopted strategies was carried out taking into account 26 variables (main, basic, temporal and spatial). Basic statistical data, correlations and analysis of variance (ANOVA) were used. Results highlight the use of a variety of strategies, of which selection depends, among others, on body composition and the level of motor abilities (speed, speed endurance and explosive strength), as well as hurdling technique. Especially, the endurance strategy appears to be th e most effective one, as it is a characteristic of best performances of many hurdlers. The analysis demonstrates that at the highest sports level the strategy of 400 m hurdles should be analyzed individually.